Avoiding sets of measure-zero in navigation transformation based controllers - Loizou, Savvas (My University, 2018)
The Navigation Transformation proposed in [Loizou (2017)] provides a novel solution to the motion and path planning problems, while enabling temporal stabilization up to a set of measure-zero of initial conditions. Since sets of measure zero are explicitly defined for a given workspace, this work proposes an additional control action that steers the system trajectories away from such sets. The provided theoretical results are backed with experimental studies.
Keywords: Navigation transformation; Time abstraction